2015
DOI: 10.18805/ijar.9594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded concentration of organic Zinc (Zinc glycinate) on antioxidants status and immune response in commercial broilers

Abstract: One hundred and twenty day old commercial broiler chicks were randomly allotted to 4 dietary groups, with 6 replicates of 5 birds in each and reared for 42 days under uniform management conditions to study the effect of organic zinc (zinc glycinate; Zn-gly) supplemented at lower levels (30, 20 and 10 ppm) on antioxidant status and immune response in comparison to NRC (1994) recommended levels (40 ppm) of Zn supplemented from inorganic source (ZnSO4). The dietary treatments were corn soybean meal basal diet sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…The CMIR against PHA-P expressed as DTH reaction was higher (P<0.05) in Zn-Prop supplemented calves compared to ZnSO 4 at both 24 and 48h of post sensitization (Table 7). Current findings are in consistent with the results of Sridhar et al (2016) who observed better (P<0.05) cell mediated immunity in Table 7: Cell mediated immune response against PHA-P (increase in skin fold thickness, mm) in buffalo calves fed zinc propionate supplemented diets.…”
Section: Serum Biochemical Parameterssupporting
confidence: 91%
“…The CMIR against PHA-P expressed as DTH reaction was higher (P<0.05) in Zn-Prop supplemented calves compared to ZnSO 4 at both 24 and 48h of post sensitization (Table 7). Current findings are in consistent with the results of Sridhar et al (2016) who observed better (P<0.05) cell mediated immunity in Table 7: Cell mediated immune response against PHA-P (increase in skin fold thickness, mm) in buffalo calves fed zinc propionate supplemented diets.…”
Section: Serum Biochemical Parameterssupporting
confidence: 91%
“…This is because there are antioxidant protection mechanisms in the body, including a series of antioxidant substances (such as MT) and antioxidant enzymes (such as SOD, GSH-Px, CAT) [ 53 ], and their expression levels represent the antioxidant ability of animal. Studies have confirmed that dietary zinc supplementation can increase the activity of T-AOC, CuZn-SOD, GSH-Px, CAT, T-SOD, and the level of MT in various tissues of chickens [ 34 , 49 , 54 , 55 , 56 ]. Consistent results were also obtained in this experiment, maternal zinc treatment increased the activity of antioxidant enzymes and the level of MT in chicken embryo liver under oxidative stress and non-oxidative stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nagalakshmi et al, (2015a &2016a) observed better antioxidant activity in rats supplemented with Zn methionine compared to Zn carbonate. Furthermore, Sridhar et al, (2016) observed improved antioxidant status of broiler chicken though reducing the Zn supplementation using organic Zn (Zn glycinate).…”
Section: Oxidative Stress Markers and Antioxidant Enzyme Activitymentioning
confidence: 99%